Optimalisasi Keuntungan pada Usaha Mikro Kecil dan Menengah (UMKM) Pempek Cik Lin Menggunakan Model Integer Linear Programming dan Software Lingo - Arif Agung Nugroho; Sahana Pramukti; Ratih Setyaningrum (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In the food industry, problems are often found in optimizing production results for maximum profits. The lack of knowledge to determine feasible and optimal solutions in entrepreneurship for UMKM can affect the income of these UMKM. In UMKM Pempek Cik Lin, several problems are faced to increase their profits, namely limited production resources and capital, resulting in less optimal production and the ability to increase profits from sales results. This case study was completed with the simplex method's linear programming integer model. A comparison was also carried out with the help of lingo software. The result of this study is that the completion of linear programming using the simplex method shows a maximum profit of Rp. 75,000 with the type of submarine pempek produced as many as ten pcs and pempek lenjer as many as ten pcs. Meanwhile, the settlement using lingo software obtained the most significant maximum profit, Rp. 85,000 with the type of pempek kapal selam produced as many as fourteen pcs and pempek lenjer as many as zero pcs. From this comparison, the most significant optimization results were obtained using lingo software so that UMKM Pempek Cik Lin has the picture needed if they have limitations in terms of production raw materials so that the business can increase their income